230 Young Scholar Presentation: Heat stress and its effects on energetics, gut integrity, and inflammation in pigs. (30th November 2020) - Mayorga, Edith J; Baumgard, Lance H
Abstract: Heat stress represents one of the costliest issues in animal agriculture as it compromises a variety of production parameters including growth and reproduction. When animals are exposed to heat stress, physiological and metabolic changes are needed to cope with the heat insult to maintain euthermia. The most well-established adaptation across species involves a marked reduction in feed intake. Additionally, heat-stressed animals alter their carbohydrate, lipid, and protein metabolism; a mechanism characterized by a paradoxical increase in circulating insulin. This altered nutrient partitioning appears to be mediated by the effects of heat stress on gastrointestinal health. Heat-stressed animals redistribute blood flow from the splanchnic bed to the periphery in a coordinated attempt to maximize heat dissipation. This circulatory adaptation reduces blood and nutrient delivery to the gastrointestinal tract which compromises intestinal infrastructure barrier. Consequently, a dysfunctional intestinal barrier allows for the translocation of dietary and microbial (i.e., lipopolysaccharide [LPS], from Gram negative bacteria) antigens from the lumen to the basolateral membrane, stimulating a local and systemic inflammatory response. Interestingly, there are remarkable metabolic and physiological similarities between animals suffering from heat stress and severe endotoxemia; in both conditions, there is an increase in circulating insulin despite marked reductions in feed intake, a scenario energetically difficult to explain. The likelihood that LPS is an insulin secretagogue explains the hyperinsulinemia we and others observe in a variety of heat stress models. Inflammation induced by LPS elicits the production of pro-inflammatory cytokines. When activated, the immune system utilizes a considerable amount of energy (glucose), which redirects nutrients away from production purposes (i.e., growth, reproduction); thus, negatively compromising animal production efficiency. Therefore, identifying strategies designed to minimize intestinal permeability, improve the immune response, and enhance animal productivity during a thermal load is of particular interest. Nutritional interventions are practical and cost-effective approaches to mitigate the detrimental effects of heat stress on animal health and productivity and to minimize agricultural economic losses.